Single-step synthesis of ZnO/TiO2 nanocomposites by microwave radiation and their photocatalytic activities - Arin J. (2014)
Zn(NO3)2·6H2O and C 4K2O9Ti·2H2O with 1:1 and 2:1 M ratios of Zn:Ti in solutions at the pH 10 were irradiated by 180 W microwave radiation for 40 min to form ZnO/TiO2 nanocomposites, new candidates for photodegradation and photoreduction in UV light with very high efficiency. Upon processing the nanocomposites at high temperatures, pure Zn 2TiO4 nanocrystals were synthesized only by the 700 °C and 3 h calcination of the 2:1 M ratio Zn:Ti precursors. © 2013 Elsevier B.V.